KONSEP ISLAM DALAM AL-TANZIL AL-HAKIM PERSPEKTIF MUHAMMAD SYAHRUR - Affandi, Abdullah (Jurnal al Hikmah, 2015)
Most of the Muslims, according Shahrur, are misled by the various ideas from classical tradition, regardless of the variety of contemporary scientific discoveries. They consider various classical scientific tradition-filled doctrine as a truth that is